Sustainable Development under the Impacts of the Fourth Industrial Revolution and the Role of Corporate Culture Renovation - Manh Quan, Nguyen; Thi Kim Chi, Nguyen; Hoang Giang, Pham (VNU Journal of Science: Policy and Management Studies, 2022)
Abstract: The impacts of scientific-technological development in the Fourth Industrial Revolution have created potentials and opportunities for the enhancement of acting capability, productivity of organizations in general and enterprises in particular. Facing the rapid changes of technology and operational modes, in order to achieve a sustainable development, corporates need to renovate their core elements such as human resources and culture. This article discuss the role of corporate culture as an instrument for responsible and sustainable business. Especially after the SARSCoV-2 pandemic, corporate culture has received the most attention over other solutions because it is both an immediate and a permanent solution in theory as well as in practice. From that, the authors also suggests some directions for the renovation of corporate culture corresponding to the current digital transformation process. Keyword : Business sustainability, corporate culture, digital culture, digital transformation, employee’s empowerment.